Canonical form for marriage: Canons 1117 nad 1118 (Roman Replies and CLSA Advisory Opinions 2007, 2007)
"This request for dispensation from the Canonical Form for Marriage for two Catholics, one of the parties being recently received into the Catholic Church, is being printed since it seems to indicate an apparent change in practice of the Congregation for Divine Worship and the Discipline of the Sacraments."